Sistem Pendukung Keputusan Seleksi Calon Putra-Putri Duta Pariwisata Menerapkan Metode VIKOR - Fendy Arisandri Hutauruk (BEES: Bulletin of Electrical and Electronics Engineering, 2023)
Tourism Ambassador which serves to promote tourism products in an area so that it is better known and attracts domestic and foreign tourists to come and enjoy tourism products in the Central Tapanuli Regency area. To produce competent Tourism Ambassadors, strict and quality selection is carried out. Due to the large number of selection participants, a decision support system was created to facilitate the assessment process. This system uses the VIKOR method to determine the value of the weighted criteria consisting of personality ethical values, general knowledge, appearance, interviews, achievements/talents, attitude in answering questions, friendliness, English and also height to find the best alternative participants. The results of the calculation are then displayed in the form of 6 alternative names of the best male and female participants. Therefore, we need a decision support system (SPK) that is able to help existing problems and make it easier to determine prospective sons and daughters of tourism ambassadors in Central Tapanuli Regency. The decision support system also functions as a supporting facility to determine prospective tourism ambassadors. With this system, it is expected to be able to get an optimal decision system. This study discusses the selection of tourism ambassador candidates by applying nine criteria. These nine criteria are personality ethics, general knowledge, appearance, interviews, achievements/talents, attitude in answering questions, friendliness, English and also height. Data analysis applied VIKOR method for weighting and criteria ranking.